MENTAL DISORDERS IDENTIFICATION APPLICATIONS SINCE EARLY USING WEB-BASED Macromedia Flash MX 2004 - Muhammad Muhammad; Melani Dewi Lusita, SKom, MMSI (Jurnal Sistem Informasi, 2006)
The growing world of computer technology so that all the problems can be solved one way is to create a "The application of functional recognition of mental disorders since the early web-based using Macromedia Flash MX 2004" which with this application we can know the symptoms of functional mental disorders and the types of disease in this application. Recognition application program based mental disorders and multimedia web becomes easier and the user is more interested in finding try out.